The dimensionality of the epistemic orientation survey and longitudinal measurement invariance for the short form of EOS (EOS-SF) - Ding, Chenchen; Fulmer, Gavin; Hoffman, Lesa; Hand, Brian; Suh, Jee K. (Frontiers in Education, 2023)
The dimensionality of the epistemic orientation survey (EOS) was examined across four occasions with item factor analysis (IFA). Because of an emphasis on the knowledge generation of epistemic orientation (EO), four factors were selected and built into a short form of EOS (EOS-SF). To track the stability of the factor structure for each factor of EOS-SF, longitudinal invariance models were conducted. Evidence for the longitudinal invariance was obtained. Researchers can choose certain factors of EOS to shape a new instrument for research purposes.